Ann Buckley (ed.), Music, Liturgy, and the Veneration of Saints of the Medieval Irish Church in a European Context (2017). - Mannion, Anne (Journal of the Society for Musicology in Ireland, 2020)
A review of Ann Buckley (ed.), Music, Liturgy, and the Veneration of Saints of the Medieval Irish Church in a European Context (Turnhout: Brepols, 2017). ISBN 9782503534701